Peningkatan Kompetensi Guru Dalam Menyusun Penilaian Berbasis Kurikulum-13 Melalui Supervisi Akademik - Nureroan, Elvis Elieser (Didaktika, 2021)
The most effective step to improve teacher competence in the preparation of assessments is through structured guidance, namely in academic supervision activities. The aims of this study were (1) to describe the implementation of academic supervision in preparing the 2013 curriculum-based assessments and (2) describe the increase in the competence of teachers of SMP Negeri 1 Inanwatan, South Sorong, West Papua Province in preparing 2013 curriculum-based assessments. This study uses a school action research design (SAR). Based on data exposure, findings, and discussion of research results on academic supervision activities, it can be concluded as follows: First, the average score of teacher competency improvement in preparing the the 2013 curriculum-based assessments in cycle I is 78 with an achievement percentage of 77.9%. The two frequencies of increasing teacher competence in compiling K-13-based assessments in cycle II the average score reached 84.8 with an achievement percentage of 84.7%. Third, in cycle I and cycle II, 1 teacher or 9.1% was able to compile 12 aspects of K-13-based assessment with a very good category at intervals of 91%-100%. In the second cycle as many as 10 teachers or 90.9% with a good category (B) at an interval of 76% - 90% score. Academic supervision activities are proven to improve the quality of teacher competence in preparing the 2013 curriculum-based assessment.Â